ATLAS-seq: a microfluidic single-cell TCR screen for antigen-reactive TCRs - Siwei Luo; Amber Notaro; Lan Lin (Nature Communications)
Abstract Discovering antigen-reactive T cell receptors (TCRs) is central to developing effective engineered T cell immunotherapies. However, the conventional technologies for isolating antigen-reactive TCRs (i.e., major histocompatibility complex (MHC) multimer staining) focus on high-affinity interactions between the TCR and MHC-antigen complex, and may fail to identify TCRs with high efficacy for activating T cells. Here, we develop a microfluidic single-cell screening method for antigen-reactive T cells named ATLAS-seq (Aptamer-based T Lymphocyte Activity Screening and SEQuencing). This technology isolates and characterizes activated T cells via an aptamer-based fluorescent molecular sensor, which monitors the cytotoxic cytokine IFNγ secretion from single T cells upon antigen stimulation, followed by single-cell RNA and single-cell TCR sequencing. We use ATLAS-seq to screen TCRs reactive to cytomegalovirus (CMV) or prostate specific antigen (PSA) from peripheral blood mononuclear cells (PBMCs). ATLAS-seq identifies distinct TCR clonotype populations with higher T cell activation levels compared to TCRs recovered by MHC multimer staining. Select TCR clonotypes from ATLAS-seq are more efficient in target cell killing than those from MHC multimer staining. Collectively, ATLAS-seq provides an efficient and broadly applicable technology to screen antigen-reactive TCRs for engineered T cell immunotherapy.